Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - Chapter Review Exercises - Page 163: 33


$$ y'= 6(4x^3-9) (x^4-9x)^5 .$$

Work Step by Step

Recall that $(x^n)'=nx^{n-1}$ Since $ y=(x^4-9x)^6$, then by the chain rule the derivative $ y'$ is given by $$ y'=6 (x^4-9x)^5(4x^3-9)=6(4x^3-9 )(x^4-9x)^5 .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.